Who Did Lancaster Castle 'Belong to'? The Duchy of Lancaster, the County and the Home Office c. 1698–1930. (2018) - Winstanley, Michael
Abstract : The Duchy of Lancaster traces its ownership of Lancaster Castle to the thirteenth century. This article explains how the Home Office came to believe that they, rather than the Duchy, owned the prison in Lancaster Castle and how they came to propose selling it to Lancashire County Council in the 1920s. It describes how the property has been managed over previous centuries and draws distinctions between the concepts of 'belonging to' and outright ownership, and between the prison and the adjacent courts, built largely on land outside the old castle walls. It then discusses how the situation was resolved and assesses the role of each of the players.